Algorithms and complexity : 10th International Conference, CIAC 2017, Athens, Greece, May 24-26, 2017, proceedings /: 10th International Conference, CIAC 2017, Athens, Greece, May 24-26, 2017, proceedings. (2017) - Unknown
No abstract available